2017
DOI: 10.1016/j.amepre.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intensity and Incidence of Metabolic Syndrome: The SUN Project

Abstract: Vigorous LTPA was significantly associated with lower risk of developing MS after a 6-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…The recommendations to achieve greater health benefits are given either by increasing the time or the energy. And as some studies show [10,11] both cardio-metabolic health and reduction in mortality will benefit most from vigorous activities, while mental health is more influenced by the time spent in PA. In addition, in our study, we found that to reduce the risk of depression, it is necessary to increase the levels of moderate physical activity above 300 min per week or perform 150 min of vigorous physical activity per week, or an equivalent combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendations to achieve greater health benefits are given either by increasing the time or the energy. And as some studies show [10,11] both cardio-metabolic health and reduction in mortality will benefit most from vigorous activities, while mental health is more influenced by the time spent in PA. In addition, in our study, we found that to reduce the risk of depression, it is necessary to increase the levels of moderate physical activity above 300 min per week or perform 150 min of vigorous physical activity per week, or an equivalent combination.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have been published reinforcing the favorable and consistent effects of LTPA on cardiometabolic disease [10,11] and cancer [12]. LTPA has beneficial effects over mental health diseases, such as depression, anxiety and stress, and also over quality of life [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies with outcomes such as metabolic syndrome, cardiorespiratory fitness, blood pressure and lipid profiles [17][18][19][20] indicate that the benefits of one minute of vigorous activity outweigh those of two minutes of moderate activity. Inverse associations between vigorous activity and obesity found in this study may be partly driven by favorable adaptations to lipid metabolism and other biological pathways.…”
Section: Discussionmentioning
confidence: 99%
“… 22 The WBV exercise can be considered a feasible, safe, and low-cost technique to the improvement of health in various populations. 19 22 Biomechanical parameters, such as the frequency and the peak-to-peak displacement of the mechanical vibration, must be considered in the WBV exercise protocols. 23 Wei et al 24 consider low frequency (20 Hz), medium frequency (40 Hz), and high frequency (60 Hz).…”
Section: Introductionmentioning
confidence: 99%